Blood for the Crown: Analyzing Army Coups and Political Upheavals in Shakespeare’s Selected Plays - Ali, Chand; Tasnim, Tamanna (International Journal of Language and Literary Studies, 2025)
This research examines military coups and political problems in some of the most renowned plays of William Shakespeare, i.e., Richard II, Henry IV, Henry VI, Richard III, Julius Caesar, Macbeth, Hamlet, and King Lear. It more or less tries to see how Shakespeare defines military coups, rebellions, revolutions for power, and what effect they have on leadership, social peace, and the human mind. By reading the plays together and reading them closely, the article identifies biting political ideas such as the overthrow of kings who were believed to be godlike, the rise of those who rise to power by violence, and the danger of being so starved for power. Many people focus on Shakespeare’s poetic reflections on kings and their rule, but fewer explore how Shakespeare shows that power is often defined and maintained through war and violence. This paper attempts to fill that gap by looking closely at what Shakespeare is describing as a political coup and violent takeover and rendering these into what was going on in Elizabethan England. This is achieved through the application of methods like close reading of the text, the study of history, and application of political philosophy while establishing how Shakespeare treats power, justice, and revolution. Lastly, the article introduces us to make a judgment about Shakespeare’s ideas on power applications today if one considers government, justice, and what finally occurs to the rebels against today’s power structure.